Case Report: Bronchial artery embolization and chemoradiotherapy for central squamous cell lung carcinoma with rapid regression - Zhou, Siqi; Zhang, Jianxin; Meng, Xue; Meng, Yingtao; Han, Xiao (Frontiers in Oncology, 2022)
Background: Interventional embolization is a common treatment for hemoptysis, one of the complications of lung cancer. However, there are no official guidelines for the use of this method in antitumor therapy. Case Description: Herein, we describe a case of a patient who was pathologically diagnosed as central squamous cell lung cancer. The patient received chemotherapy, interventional embolization and radiotherapy successively. The tumor regressed rapidly within 48 hours of receipt of interventional embolization. Furthermore, the tumor decreased by more than 50% in size within 7 days during radiotherapy. Unfortunately, the patient has since developed lymph node metastases and remains under treatment. Conclusions: Thus, finding the suitable blood vessel embolized may be a suitable option to reduce the local tumor load and can be considered as antitumor therapy in combination with other treatments. The patient's theoretical hypoxia state after interventional therapy still produced a good tumor regression after radiotherapy. However, so far, no related studies have reported the changes of tumor immune microenvironment in human body after intervention and radiotherapy.